A miniature cylindrical differential mobility analyzer for sub-3 nm particle sizing. (April 2017) - Cai, Runlong; Chen, Da-Ren; Hao, Jiming; Jiang, Jingkun
Abstract: Effective particle sizing is one of the limitations in measuring sub-3 nm aerosol. In this study we developed a miniature cylindrical differential mobility analyzer (mini- cyDMA) for sub-3 nm particle sizing. The construction of the miniature cylindrical DMA, stemmed from the cost-effective DMA (cDMA) developed by Mei et al. (2011), enables it to be operated at higher sheath flowrate than the cDMA. To keep the sheath flow laminar in the DMA classification region for the flowrate up to 30 l per minute (lpm) for better matching the flowrate required by the aerosol detector while having a good sizing resolution, the DMA components such as the inlet for sheath flow, nylon screen for flow laminarization, and the chambers for polydisperse aerosol flow inlet and excess flow exit were re-designed in the mini- cyDMA. Transfer function of the mini- cyDMA was evaluated using tetra-alkyl ammonium cations with electrical mobility diameters of 1.16 nm, 1.47 nm and 1.78 nm, respectively. A data inversion routine based on an empirical diffusive transfer function was used to obtain the transfer function of the mini- cyDMA. When classifying 1.47 nm particles at the aerosol-to-sheath flow ratio of 2.5/25 lpm, the penetration efficiency and the sizing resolution of the mini- cyDMA are 0.21 and 5.7, respectively. The mini- cyDMA was deployed to characterize newly-formed atmospheric particles and flame-generated nascent soot particles. Highlights: A miniature cylindrical DMA for sizing sub-3 nm particles was developed. Its transfer function and penetration efficiency were evaluated. Measured new particles in the atmosphere and nascent soot particles in flames.